Protective Role of Religious Involvement Against Depression and Suicidal Ideation Among Youth with Interpersonal Problems - Cole-Lewis, Yasmin C. (Journal of religion and health, 2016)
This study examined religious involvement—private religious practices (PRP), organizational religiousness (OR), and religious support (RS)—in relation to depressive symptoms and suicidal ideation (SI) and its protective role, considering youths’ school and parent-family connectedness. Youth, ages 12-15 (n = 161), were screened for peer victimization, bullying perpetration, and low social connectedness, and assessed for depressive symptoms, SI, school connectedness, parent-family connectedness, and religious involvement. Results indicated PRP and RS were associated with lower levels of depressive symptoms; PRP and OR were associated with less SI. Controlling for connectedness, PRP remained associated with less SI only. Results suggest the importance of considering religious involvement as a target of youth depression and suicide prevention interventions.